STUDI KINERJA JALAN AKIBAT HAMBATAN SAMPING DI JALAN TIMOR RAYA DEPAN PASAR OESAO KABUPATEN KUPANG - Funan, Gideon Antoni; Cornelis, Remigildus; Hunggurami, Elia (Jurnal Teknik Sipil, 2014)
Poor land use management systems and transportation management systems nowadays more visible in various areas in the East often lead to complicated problems. One segment of Timor Raya street is often jammed in Oesao Market area, this happens because of the many traders who trade on the curb lane to the shoulder of the road . In addition the number of vehicles parked on the shoulder of the road further aggravate the condition of the road especially at busy times. From the results of the analysis indicate that the side friction road values were very high at 3998.60 events caused by the presence of market activity in the left and right side of the road, too many parked vehicles and pedestrian which is reducing the effective width of the road that directly affect the performance of the road itself . This problem caused actual speed at the road segment becoming increasingly low at 23,49 km/h with average travel time of 0.0125 hours . The results of analysis show that the level of service is at grade E. The biggest factor that is very influential in determining the level of service at the location is the market activity at the sides of the which increase the side friction